Proteomic and lipidomic analysis of exosomes derived from ovarian cancer cells and ovarian surface epithelial cells - Lin Cheng; Kun Zhang; Yunan Qing; Dong Li; Manhua Cui; Peng Jin; Tianmin Xu (BMC, 2020)
Abstract Background The limitation of current biomarker of early stage ovarian cancer and the anatomical location of ovarian (depths of the pelvic) make ovarian cancer difficult to be detected in early stage. Growing evidence shows exosomes as key information transmitters, it carried molecules, such as miRNAs, proteins, lipids, double-stranded DNA have been reported as promising biomarkers in many diseases. However, little is known about the protein and lipid composition of ovarian cancer. Methods Here, we report proteomic and lipidomic analysis of exosomes derived from ovarian cancer cells (SKOV-3) and ovarian surface epithelial cells (HOSEPiC). Results A total of 1433 proteins and 1227 lipid species were identified from two cell line derived exosomes. Several lipid species and proteins significantly differ in SKOV-3 derived exosomes compared to those from HOSEPiC. For example, we noted that ChE and ZyE species were in general more abundant in exosomes from SKOV-3 than from HOSEPiC; Collagen type V alpha 2 chain (COL5A2) and lipoprotein lipase (LPL) were significantly higher in SKOV-3 derived exosomes than HOSEpic (p < 0.05). Conclusions Our research indicates the promising role of exosomal proteins and lipids in the early diagnosis of ovarian cancer.